2012
DOI: 10.1007/s00240-012-0467-1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating ESWL-induced renal injury based on urinary TNF-α, IL-1α, and IL-6 levels

Abstract: Extracorporeal shockwave lithotripsy (ESWL) has dramatically changed the treatment of urinary lithiasis and has been the first treatment option for the majority of patients for more than two decades. Despite its significant benefits, it induces acute renal injury that extends from the papilla to the outer cortex. We evaluated the severity of the inflammatory response to ESWL by measuring the urinary excretion of the cytokines TNF-α, IL-1α, and IL-6. The study included 21 selected patients and 14 control subjec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 12 publications
0
19
0
Order By: Relevance
“…SWL treatment may induce inflammation and increase the fragility of the ureter at the location of the stone. Goktas et al showed that urine inflammatory cytokines increased after SWL treatment (11). Thus, unsuccessful SWL treatment seems to increase the risk of avulsion.…”
Section: Discussionmentioning
confidence: 99%
“…SWL treatment may induce inflammation and increase the fragility of the ureter at the location of the stone. Goktas et al showed that urine inflammatory cytokines increased after SWL treatment (11). Thus, unsuccessful SWL treatment seems to increase the risk of avulsion.…”
Section: Discussionmentioning
confidence: 99%
“…They reported a significant increase in the level of IL-6 during early phase (24 hours after ESWL). They also found the same results about levels of IL-1ɑ during a 14-day period (12). Also, Dundar et al revealed a significant increase in the level of IL-1ɑ in the early phase (24 hours after ESWL) and IL-6 over a 14-day course in patients underwent ESWL (22).…”
Section: Discussionmentioning
confidence: 58%
“…These waves can lead to damage to the renal artery directly. It may also cause an inflammatory response, known as ESWL-induced nephritis (12,13). Considering the importance of this issue, we studied many parameters neglected in other studies including sex, size, location and side of stone in urinary tract.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations